If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (n + -3) * 9 = 90 Reorder the terms: (-3 + n) * 9 = 90 Reorder the terms for easier multiplication: 9(-3 + n) = 90 (-3 * 9 + n * 9) = 90 (-27 + 9n) = 90 Solving -27 + 9n = 90 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '27' to each side of the equation. -27 + 27 + 9n = 90 + 27 Combine like terms: -27 + 27 = 0 0 + 9n = 90 + 27 9n = 90 + 27 Combine like terms: 90 + 27 = 117 9n = 117 Divide each side by '9'. n = 13 Simplifying n = 13
| 65+10x=6 | | x-1+x+x+3=32 | | (n-5)*6=48 | | 3(7x-1)=5(3x+3) | | 25=2c-9 | | 9x-4(3x-2)=4 | | 5x=2(x+30) | | 3b+15=27 | | m+2=15 | | 9x-19=7x+11 | | 15x^3+25x^2-60x= | | 8t-11=5t+19 | | -2(18-3t)=7y+2y | | -(5y+2)-(-4y-8)=1 | | 4-x=-5 | | 2(x+30)= | | 6n-2=14 | | 52=(3x+6)+(6x+22) | | 3(5+x)=31+x | | 51=(2+7x)+(20x+1) | | 50=(8x-6)+(13x+9) | | 87=(8x+2)+(8x+5) | | x-9= | | 8n+8=16 | | 95=(3+8x)+(14x+4) | | 8n+2=16 | | 8n+6=16 | | 8n+6=24 | | 3x+2=7.5 | | 9x+7y=10 | | 57=(9x-2)+(23x-1) | | x+2(x+1)=35 |